2019
DOI: 10.1039/c9qm00132h
|View full text |Cite
|
Sign up to set email alerts
|

Soft nanohand grabs a growing nanoparticle

Abstract: Artificial, organic, and soft four-finger nanohands can selectively pick up growing nanogold of a particular size. Their structures were characterized and modelled by theoretical calculations. This prototype nanomachine provides the fundamental understanding needed to sort out nanosized products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…In summary, we demonstrated a method to grow MnSi films on Al 2 O 3 by conventional magnetron sputtering with a relatively low vacuum chamber. Developing a facile way to fabricate various nanostructures is imperative [34,35]. The spectroscopic and morphological analyses confirmed that the as-deposited MnSi films have a polycrystalline nature with a highly uniform and low roughness surface.…”
Section: Resultsmentioning
confidence: 99%
“…In summary, we demonstrated a method to grow MnSi films on Al 2 O 3 by conventional magnetron sputtering with a relatively low vacuum chamber. Developing a facile way to fabricate various nanostructures is imperative [34,35]. The spectroscopic and morphological analyses confirmed that the as-deposited MnSi films have a polycrystalline nature with a highly uniform and low roughness surface.…”
Section: Resultsmentioning
confidence: 99%
“…where E ZnO and are the energy of ZnO molecule and C 3 N monolayer before doping, and is the energy of ZnO-C 3 N structure. When the close-range “bonding” between atoms occurs in the extended atomic structure, the total energy is reduced and resulting in a negative E form [ 50 ]; the structure with the largest E form is selected for adsorption and further analysis.…”
Section: Resultsmentioning
confidence: 99%
“…An alternate dendron motif based on CuAAC-'clicked' triazols [59] was proposed. [60] Upon functionalizing the focal point of the dendron with a disulfide as anchor, it was shown that the resulting AuNPs were indeed stabilized by a single ligand. The parent ligands, functionalized with free acetylene or row dispersity suggesting a discrete number of ligands coating the particle.…”
Section: Pre-polymerized Ligandsmentioning
confidence: 99%